Liwetan Gerhana Tradition for Pregnant Women in the Perspective of Islamic Law and Community Culture (Case Study in Klinterejo Sooko Mojokerto) - Istiqomah Istiqomah (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2024)
This study aims to examine the religious and cultural values embedded in the practice of Liwetan Gerhana, as well as its interpretation within Islamic law. Traditions are customs passed down through generations, each carrying profound significance for its practitioners. Often, these traditions are deemed sacred and essential to uphold. This research investigates the Liwetan Gerhana tradition for pregnant women, considering both Islamic legal perspectives and the local cultural context. This tradition represents a cultural heritage with deep meaning for the practising community, especially for pregnant women, who are seen as requiring protection and blessings. In Islamic jurisprudence, a solar or lunar eclipse (gerhana) is regarded as a manifestation of God’s greatness, typically observed through worship rather than specific rituals. The research method employed is fieldwork, with data collected via in-depth interviews and direct observation in Klinterejo Village, Sooko. The tradition is recognised not only as a cultural ritual but is also seen as compatible with Islamic principles, promoting the health and well-being of pregnant women. Findings indicate that, while this tradition has strong cultural roots, the community has successfully harmonised it with Islamic teachings, resulting in a dynamic syncretism widely accepted by the community. This fusion of culture and religion demonstrates the community’s ability to adapt to contemporary changes while preserving its cultural identity.